The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jms.2975
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the bisulfite anion (HSO3, m/z 81) upon collision‐induced dissociation of anions derived from organic sulfonic acids

Abstract: In the negative-ion collision-induced dissociation mass spectra of most organic sulfonates, the base peak is observed at m/z 80 for the sulfur trioxide radical anion (SO(3) (-·) ). In contrast, the product-ion spectra of a few sulfonates, such as cysteic acid, aminomethanesulfonate, and 2-phenylethanesulfonate, show the base peak at m/z 81 for the bisulfite anion (HSO(3) (-) ). An investigation with an extensive variety of sulfonates revealed that the presence of a hydrogen atom at the β-position relative to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…To the best of our knowledge, stable isotopes of the oxidized sulphur-containing amino acids methionine sulfone and cysteic acid, which are present in oxidized samples, have never before been used as internal standards. They can easily be synthesized [ 28 ] and we have in this study successfully used them as internal standards to significantly improve the quantification of these two amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, stable isotopes of the oxidized sulphur-containing amino acids methionine sulfone and cysteic acid, which are present in oxidized samples, have never before been used as internal standards. They can easily be synthesized [ 28 ] and we have in this study successfully used them as internal standards to significantly improve the quantification of these two amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope labeled methionine sulfone and cysteic acid were not commercially available and were prepared in our lab from labeled methionine and cysteine according to the procedure by Jariwala et al [ 28 ]. In brief, a performic acid mixture was prepared by adding 9 mL of formic acid and 1 mL of hydrogen peroxide (30%).…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies have reported that these two structurally significant product ions are commonly observed during mass spectrometric analysis of sulfonic acids. 26 The MS/MS product ion ratios ranged from 1 to 8% for all of the standards and samples analyzed. For regulatory analyses, all ratios must be within 10% absolute of the value, with a signal-to-noise ratio of >3:1.…”
Section: Methods Developmentmentioning
confidence: 99%
“…In accordance with previous collisionally-activated dissociation experiments, PF of the Ph-SO3  anion proceeds via SO3  loss. 6,29 The spectrum obtained by plotting the SO3  ion yield vs. the excitation energy is identical to the one recording the intensity of neutrals corresponding to the temporal profile edge, i.e. where the signal is a measure of neutrals originated in a dissociation process (having an excess of kinetic energy).…”
Section: Phenylsulfonate Anion (Ph-so3  )mentioning
confidence: 99%